Economic cost evaluation on the viability of offshore wind turbine farms in Nigeria. (November 2016) - Effiom, S.O.; Nwankwojike, B.N.; Abam, F.I.
Abstract: The paper presents an economic cost evaluation on the feasibility of offshore wind turbine (OWT) farms development in Nigeria, using a 500 MW OWT farm as an incident study. A developed model was used to evaluate the economic cost of the OWTs at different phases of the project. Additionally, the effect of the cost drivers at the changed phases of the OWTs was studied correspondingly. Results obtained showed that over 50% of the OWT project cost emanated from CAPEX while a value less than 50% came from OPEX. However, further analysis indicates at maximum power of 4 MW a 4.95% diminution in LCOE. For comparable power rating (PR) between 5 ⩽ PR ⩽ 6 MW, a 2.7% reduction in LCOE exists. Cost stability was apparent at a growth of WTs between 300 ⩽ WT ⩽ 500 MW. The study also observed a decrease in LCOE for all development stages of the OWT while a decrease in the CMS detectability was considered marginal. Subsequently, it can be inferred that Nigeria has the potential for OWT farm expansion. However, the demonstrated model was appropriate for handling preliminary variations in OWT studies.